ZAKAT DALAM PERSPEKTIF KEBIJAKAN FISKAL - Muh. Arafah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Zakat is an important part of a wealth distribution system given by God in a fair and detailed manner for the benefit of humanity. Islamic principles of fiscal policy aim at developing a society based on the balanced wealth distribution by placing material and spiritual values at the same level, equally. One of the goals of zakat expenditure in Islamic fiscal policy is to provide for the needy and poor people in addition to paying the zakat collectors.